Queer - Getsy, David (Whitechapel : documents of contemporary art, 2016)
"Rather than a book of queer theory for artists, this is a book of artists' queer tactics and infectious concepts. In the first such anthology to be centred on artists' writings, numerous conversations about queer practice are brought together from diverse individual, social and cultural contexts. Together these texts describe and examine the ways in which artists have used the concept of queer as a site of political and institutional critique, as a framework to develop new families and histories, as a spur to action, and as a basis from which to declare inassimilable difference"--Back cover.
Keywords: LGBTQIA2+; approches et analyses; arts; arts visuels et médiatiques; cours; critique institutionelle; critique politique; discipline; har4600; identités LGBTQIA2+; intersectionnalité; militance; pratique artistique; premier cycle; queer; thématiques; écrits d'artiste